Effectiveness of Bawaslu's Supervision Function on Election Participation in Gorontalo Regency - Abdul, Hamzah; Darmawati, Darmawati; Makkulawuzar, Kingdom (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
General elections are a very important thing in democracy. Like two sides of a coin that cannot be separated from each other, the same applies to elections and democracy. The two cannot be separated. If there is a general election then there is democracy. The existence of an election supervisory institution (Bawaslu) which is regulated in Law of the Republic of Indonesia Number 7 of 2017 concerning General Elections is very important in determining the effectiveness of the election implementation process. The aim of the research is to find out the role and function of BAWASLU in holding General Elections and to find out the factors that influence the existence of Gorontalo Regency Bawaslu in holding General Elections. The role and function of Bawaslu in organizing General Elections is based on the position of the position in the form of authority and obligations, while function refers to the duties held by that position, so that the duties and functions of Bawaslu refer to the provisions of Law of the Republic of Indonesia Number 7 of 2017 concerning General Elections, namely in Paragraph 3 of Article 101 and Article 102 concerning duties, Article 103 concerning authority and Article 104 concerning the obligations of Regency/City Bawaslu. Factors influencing the effectiveness of the Gorontalo Regency Bawaslu in holding general elections. People who think pragmatically think that elections are only at the time of voting and do not focus on the programs offered by the people's representative candidates who are taking part in the elections.